Caracterização genética de vacas leiteiras por meio de marcadores moleculares e suas implicações na composição e qualidade do leite - Campos, Miguel ângello da Silva Fernandes (2011)
The objective of this study was to identify DNA polymorphisms at the genes leptin, β-lactoglobulin and pituitary-specific transcription factor in three genetic groups of Holstein x Guzerat dairy cows and investigate the relationship between their genotypes and the composition and quality of milk of dairy cows. Samples were collected in August 2009, being 113 blood samples from lactating crossbred cows and 58 milk samples. For analysis of DNA polymorphisms blood samples were collected, analyzed later in the Genetic Laboratory affiliated to the Zootechny Institute of São Paulo and individual milk samples were collected according to standards established by the laboratory of Management Program of Northeast Dairy Herds (PROGEN), at Federal Rural University of Pernambuco (UFRPE) for analysis of milk composition and quality. The characterization of genotypes was performed by PCR-RFLP, for which were designed specific primers for each studied gene and restriction enzymes Kpn2I, HaeIII and HinfI that cut the DNA of the following genes: leptin, β-lactoglobulin and a PIT, respectively. The leptin estimate genotypic frequence were CC 0.112, TT 0.225 and CT 0.661, for β-lactoglobulin were AA 0.136, AB 0.323 and BB 0.539, and for PIT were ++ 0.655, -- 0.311 and +- 0.032. The results show that the population is in Hardy-Weinberg disequilibrium for leptin, β-lactoglobulin and a PIT due to excess of heterozygotes in the population, however, as these genes are associated with the milk production it is considered that the animals have genetic potential for milk production in the Brazilian semi-arid conditions. Through the characterization of the studied herd there were not found implications of the polymorphism of leptin, β-lactoglobulin and PIT in the composition and quality of milk from cows in the different genetic groups 1/2, 3/4 and 7/8 Holstein x Guzerat. Key words: β-lactoglobulin, crossbred cows, leptin, PCR-RFLP, PIT1, semi-arid.